Experiences of partners of professional nurses venting traumatic information - Tinda Rabie; Melanie Wehner; Magdalena P. Koen (AOSIS, 2018)
Background: Professional nurses employed in trauma units encounter numerous stressors in their practice environment. They use different strategies to cope with this stress, including venting traumatic information to their partners and other family members.   Aims: To describe how partners of professional nurses cope with traumatic information being vented to them.   Methods: A qualitative research method with an interpretive descriptive inquiry design was used to explore, interpret and describe the coping experiences of the nurses' partners. Purposive sampling was used to select a total of 14 partners, but only ten participated in semi-structured interviews. Tesch's eight steps of open coding were used for data analysis.   Results: Four main themes were identified indicating adaptive and maladaptive coping skills, namely partners' experiences of traumatic information vented to them; partners' coping activities; reciprocal communication and relationship support between partners and nurses; and resilience of partners to deal with the nursing profession.   Conclusion: Partners employed different ways to cope with traumatic information. It was essential for partners and nurses to be supported by nurses' practice environments and to develop resilience to fulfil reciprocal supportive roles in their relationships.